Ethnic differences in overweight and obesity and the influence of acculturation on immigrant bodyweight: evidence from a national sample of Australian adults - Karen Menigoz; Andrea Nathan; Gavin Turrell (BMC, 2016)
Abstract Background Despite growing international migration and documented ethnic differences in overweight and obesity in developed countries, no research has described the epidemiology of immigrant overweight and obesity at a national level in Australia, a country where immigrants comprise 28.1 % of the population. The aim of this study was to examine ethnic differences in body mass index (BMI) and overweight/obesity in Australia and the influence of acculturation on bodyweight among Australian immigrants. Methods Data from the national Household Income and Labour Dynamics in Australia (HILDA) survey were used to examine mean BMI and odds of overweight/obesity comparing immigrants (n = 2 997) with Australian born (n = 13 047). Among immigrants, acculturation differences were examined by length of residence in Australia and age at migration. Data were modelled in a staged approach using multilevel linear and logistic regression, controlling for demographic and socioeconomic variables. Results Relative to Australian born, men from North Africa/Middle East and Oceania regions had significantly higher BMIs, and men from North West Europe, North East Asia and Southern and Central Asia had significantly lower BMIs. Among women, the majority of foreign born groups had significantly lower BMIs compared with Australian born. Male and female immigrants living in Australia for 15 years or more had significantly higher BMIs and increased odds of being overweight/obese respectively, compared with immigrants living in Australia for less than 5 years. Male immigrants arriving as adolescents were twice more likely to be overweight/obese and had significantly higher BMIs than immigrants who arrived as adults. Male and female immigrants who arrived as children (≤11 years) had significantly higher odds of adult overweight/obesity and BMIs. Conclusions This study provides evidence of ethnic differences in overweight and obesity in Australia with male immigrants from North Africa/Middle East and Oceania regions being particularly vulnerable. In addition, this study suggests that greater acculturation may negatively impact immigrant bodyweight and recently arrived immigrants as well as those who arrive as children or adolescents may benefit from obesity prevention intervention. Public health policy targeted at and tailored to these immigrant cohorts will assist in the multi-pronged approach required to address the obesity epidemic.